A Forgotten History: A Historical Overview of Kuilsriver Primary School 1908 – 2023 (Yesterday & Today Journal for History Education in South Africa and abroad, 2023)
This article focuses on the history of Kuilsriver Primary School as it is known today. Whilst this specific school has a very interesting, sometimes difficult, but also a very proud background, not many people in Kuilsriver know and understand its history. This year,2023, the school is 115 years old. It is really a remarkable achievement for an institution which had to endure extreme hardships through its history. Kuilsriver Primary School, as it is known today, was first called Kuilsrivier Laer Kleurling Skool. This name was given to the school long before legalised apartheid came into being in South Africa. Currently there is no publication on the history of the school. The school opened its doors in January 1908 in Van Riebeeck Road, the main road of Kuilsriver. The placement of the school was a welcome relief to the learners of Brackenfell and Bottelary who had to walk almost six km to the nearest school namely, SareptaPrimary School. After 1948 the country experienced the draconian political system called Apartheid. The area where this school was located was proclaimed as a white area in 1958. The school was therefore removed and relocated to the coloured area of Sarepta. Various attempts were made to disaffirm the existence of the school in the main road. The school also experienced a name change to Jan Bosman Primary School in 1970 but reclaimed the original name in 2011. The old school building structure in the main road of Kuilsriver was demolished in January 1970. The only proof that is left of the school building is a photo of the school.The purpose of this article is to put the school’s history into perspective in the Kuilsriver area as well as in the broader South African context as Kuilsrivier was part of the early Cape Colony. This article also refers to a similar situation regarding the relocation of a coloured school in Carnarvon in the Northern Cape.
Keywords: Rhenish; Mission; Kuilsrivier Laer Kleurling Skool; Group Areas Act; Disaffirm; Ceased; Apartheid; Carnarvon; Relocation; Coloured; Primary schools; History of education; Coloured education